Screening for hydroxyethyl starch (HES) doping in sport - Scalco, F. B.; Simoni, R. E.; de Oliveira, M. L. C.; Gomes, L. N. L. F.; Neto, F. R. A. (Journal of Science and Medicine in Sport, 2010)
The artificial colloid hydroxyethyl starch (HES) is among the most frequently used plasma volume expanders in the medical field. However, in 1998, its misuse by the athletic community was officially reported and since 2000, HES is prohibited by the International Olympic Committee (IOC). Therefore, several methods enabling the detection of HES in urine were developed, most based on gas chromatography-mass spectrometry (GC-MS). In the present work, a simple and low-cost screening method, intended to reduce the number of samples to be analysed by GC-MS, was developed. The method is based on the acid hydrolysis of HES and detection of the resulting glucose and hydroxyethyl glucose derivatives by Benedict's reaction (reduction of copper sulfate to brick-red cuprous oxide by glucose and/or derivatives). Samples considered suspect were submitted to GC-MS analysis for identification of HES. The method was successfully applied for screening of HES in 2627 urine samples from 1346 Brazilian soccer players and 1281 athletes from the Pan-American Games (Rio de Janeiro, 2007); 71 (2.7%) samples, considered suspect, were submitted to GC-MS, but no positive results were found. Moreover, a thin layer chromatography (TLC) method was adapted for visualisation of the characteristic band pattern of HES hydrolysis products. The results indicate that the methods are efficient and useful for the screening of HES in urine.